Evasão nos cursos de licenciatura do Instituto Federal de Educação, Ciência e Tecnologia de Minas Gerais - Tatiana Lage de Castro (2019)
This research proposed to analyze the problem of student dropout in higher education offered by Federal Institutes of Education, Science and Technology. Despite the expansion in the provision of teacher education and the need to fill the deficit of qualified teachers in Brazil, the Federal Institutes have been presenting high rates of dropout in undergraduate courses. This problem, not deeply studied in the Brazilian academic environment, guides the following research question: What factors of students, courses and vocational education institutions are associated with the dropout process in the teacher education programs offered by Federal Institutes? With this question in mind, the general objective of the research was to identify and discuss, from the perspective of dropout students, the factors associated with their processes of dropping out from their courses. The degrees in Physics, Biological Sciences and Computer Science were focused, specifically in the Federal Institute of Minas Gerais (IFMG) campuses of Bambuí, Congonhas and Ouro Branco. The research was grounded on theoretical approaches on teacher education through the interlocution of authors who discuss critical-reflexive education, as well as theories about the dropout process and the student integration in higher education. The research, having a qualitative approach, used semi-structured interviews, structured questionnaires, and documentary research as methods of data collection. Content analysis was used to interpret the data collected. The option for the qualitative method allowed the deep understanding of the problem, approaching the dropout process from the moment that students choose the teacher education program to the point where they drop out and then reflect on the set of their experiences. From the research results, this work highlights that the dropout problem results from the interaction among multiple factors (social, personal, teaching career) and that the decision of dropping out, even representing an initial feeling of failure for the students, it does not mean a definitive disruption with their intention to attend higher education. In this way, this work provides – to public agents, the academic community and the society in general – a conceptual and empirical basis that can help to address the student dropout problem and promote its prevention.